Dose-Dependent Effect of Smoking on Fertility Status among Men in Gaza Strip, Palestine - Amal Dhair; Yehia Abed (Dubai Medical Journal)
Introduction: Tobacco smoking is constantly increasing mainly in developing countries and accounts for many morbidities and mortalities. Several studies have addressed the effect of smoking on male reproductive mechanism, particularly semen quality, but the effect of smoking behavior remained inconclusive. The aim of this study was to explore the relationship of tobacco smoking status, intensity, and duration between infertile and fertile men and other accompanying genitourinary conditions. Methods: Through a case-control study, 160 infertile couples were recruited from in vitro fertilization centers in Gaza Strip. Correspondingly, another 160 fertile couples were selected from governmental clinics and residentially matched with cases. The probable stratified random technique for 2017/2018 patient’s registries was performed. Both cases and controls were interviewed with a self-constructed questionnaire. Descriptive analysis, logistic regression, and the Cochran-Mantel-Haenszel test were deployed statistically with a significant level set on p = 0.05. Results: The mean age of cases and controls was 35.7 ± 10 and 34.9 ± 5 years, respectively, where 70 and 59%, respectively, were refugees; 52 and 43%, respectively, had university education; and 10.6% compared to 5.6%, respectively, earn >USD 720/month. Active smoking was detected among 38% of infertile men and 42.5% of fertile men. Nevertheless, passive smoking (52.5% infertile and 37.5% fertile) and smoking duration >2 years (85.2% infertile and 69.1% fertile) showed a positive significant relationship (p = 0.007 and p = 0.030, respectively). Furthermore, 34 and 49% of all infertile smokers showed a dose-dependent effect (odds ratio [OR]: 2.98, p = 0.023 for 6–10 cig/day and OR: 3.68, p = 0.004 for >10 cig/day), mainly in nonobstructive causes (OR: 4.26, p = 0.040 for 6–10 cig/day and OR: 5.52, p = 0.004 for >10 cig/day). Varicocele was more likely to occur among passive smokers (p = 0.024), smoking >10 cig/day (p = 0.038), and for >2 years (p = 0.024). Recurrent genitourinary tract infection was 3 times more among infertile passive smokers (OR: 2.96, 95% confidence interval: 1.38–6.32, and p = 0.005). Adjustment for age and refugee status showed 3.5 times risk for passive smoking, more than 9 times risk for former smokers, and 2.8 risk when smoking >5 cig/day. Conclusion: Smoking more than 5 cigarettes/day and for >2 years duration or exposure to passive smoking hold an increased risk on the fertility status of men. More global and national efforts need to be directed to controlling and eliminating tobacco smoking.